Role of estrogen receptors in health and disease - Chen, Peng; Li, Bo; Ou-Yang, Ling (Frontiers in Endocrinology, 2022)
Abstract: Estrogen receptors (ERs) regulate multiple complex physiological processes in humans. Abnormal ER signaling may result in various disorders, including reproductive system-related disorders (endometriosis, and breast, ovarian, and prostate cancer), bone-related abnormalities, lung cancer, cardiovascular disease, gastrointestinal disease, urogenital tract disease, neurodegenerative disorders, and cutaneous melanoma. ER alpha (ERα), ER beta (ERβ), and novel G-protein-coupled estrogen receptor 1 (GPER1) have been identified as the most prominent ERs. This review provides an overview of ERα, ERβ, and GPER1, as well as their functions in health and disease. Furthermore, the potential clinical applications and challenges are discussed.